Clinical Features, Genetic Findings, and Risk Stratification in Arrhythmogenic Right Ventricular Cardiomyopathy: Data From a Brazilian Cohort. (31st January 2023) - Quintella Sangiorgi Olivetti, Natália; Sacilotto, Luciana; Wulkan, Fanny; D'Arezzo Pessente, Gabrielle; Lombardi Peres de Carvalho, Mariana; Moleta, Danilo; Tessariol Hachul, Denise; Veronese, Pedro; Hardy, Carina; Pisani, Cristiano; Wu, Tan Chen; Vieira, Marcelo Luiz Campos; et al.
Abstract : Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC), a rare inherited disease, causes ventricular tachycardia, sudden cardiac death, and heart failure (HF). We investigated ARVC clinical features, genetic findings, natural history, and the occurrence of life-threatening arrhythmic events (LTAEs), HF death, or heart transplantation (HF-death/HTx) to identify risk factors. Methods: The clinical course of 111 consecutive patients with definite ARVC, predictors of LTAE, HF-death/HTx, and combined events were analyzed in the entire cohort and in a subgroup of 40 patients without sustained ventricular arrhythmia before diagnosis. Results: The 5-year cumulative probability of LTAE was 30% and HF-death/HTx was 10%. Predictors of HF-death/HTx were reduced right ventricle ejection fraction (HR: 0.93; P =0.010), HF symptoms (HR: 4.37; P =0.010), epsilon wave (HR: 4.99; P =0.015), and number of leads with low QRS voltage (HR: 1.28; P =0.001). Each additional lead with low QRS voltage increased the risk of HF-death/HTx by 28%. Predictors of LTAE were prior syncope (HR: 1.81; P =0.040), number of leads with T wave inversion (HR: 1.17; P =0.039), low QRS voltage (HR: 1.12; P =0.021), younger age (HR: 0.97; P =0.006), and prior ventricular arrhythmia/ventricular fibrillation (HR: 2.45; P =0.012). Each additional lead with low QRS voltage increased the risk of LTAE by 17%. In patients without ventricular arrhythmia before clinical diagnosis of ARVC, the number of leads with low QRS voltage (HR: 1.68; P =0.023) was independently associated with HF-death/HTx. Conclusions: Our study demonstrated the characteristics of a specific cohort with a high prevalence of arrhythmic burden at presentation, male predominance, younger age and HF severe outcomes. Our main results suggest that the presence and extension of low QRS voltage can be a risk predictor for HF-death/HTx in ARVC patients, regardless of the arrhythmic risk. This study can contribute to the global ARVC risk stratification, adding new insights to the international current scientific knowledge.